OBSERVING THE PROCESS OF LEARNING TO READ THE QURAN AT ELEMENTARY SCHOOL - Muhammad Yusuf Ihsan; Udin Supriadi; Agus Fakhruddin (Department of Pendidikan Guru Madrasah Ibtidaiyah Universitas Islam Negeri Alauddin Makass, 2023)
Abstract The educational issue of learning to read Qur'an is currently growing. The number of students who still cannot read Qur'an following the rules is the main problem. This study describes the learning process of reading Qur'an at Darul Hikam Elementary School Bandung. A qualitative approach with case study method was used in this research. Data were obtained through observation, interview, and document study. The results of the data were processed using data reduction, data display, and conclusion drawing. The research findings show that the learning process of reading Qur'an at Darul Hikam Elementary School used the Teacher-Centered Learning pattern and implemented various learning methods at each grade level. The learning results show that students can read Qur'an in the